Expression of Concern: MiRNA‐218 regulates osteoclast differentiation and inflammation response in periodontitis rats through Mmp9. (15th January 2019) - Guo, Jie; Zeng, Xuemin; Miao, Jie; Liu, Chunpeng; Wei, Fulan; Liu, Dongxu; Zheng, Zhong; Ting, Kang; Wang, Chunling; Liu, Yi
Abstract: Periodontitis is a multiple infection and inflammatory disease featured by connective tissue homeostasis loss, periodontal inflammation, and alveolar bone resorption. MicroRNAs (miRNAs) are involved in the mediation of a large scale of pathological processes. Here, we show that miRNA‐218 provides protective effect on periodontitis via regulation of matrix metalloproteinase‐9 (Mmp9). This pathway is aberrant in periodontium from rats with periodontitis and human periodontal ligament progenitor cells stimulated by lipopolysaccharide, with downregulation of miR‐218 and higher levels of Mmp9 compared with periodontium from healthy rats and cells without stimulation. Overexpression of miR‐218 can suppress the degradation of Collagen Types I and IV and dentin sialoprotein (DSP), attenuate osteoclast formation, and inhibit the secretion of proinflammatory cytokines. On the other hand, overexpression of Mmp9 promotes the degradation of Collagen Types I and IV and DSP as well as RANKL‐induced osteoclast formation and elevates inflammatory factors levels. Furthermore, the inhibitory effect of miR‐218 was prevented by rescuing the Mmp9 expression. In addition, we also have showed that miR‐218 was able to attenuate bone resorption and inflammation in a periodontitis rat model. Collectively, our findings therefore suggest that miR‐218 acts as a protective role in periodontitis through the regulation of Mmp9.